2015
DOI: 10.1016/j.pmedr.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain in freshman college students and perceived health

Abstract: BackgroundWe determined body weight increase in first year Dutch college students. We had the objective to determine whether the awareness of the unhealthy lifestyle raised concerns and willingness to change habits.MethodsBody weight, heartbeat, BMI, body fat percentages, and blood pressure values were collected from 1095 students. Comprehensive statistical analysis was performed on the data.ResultsThe students had a mean weight gain of 1.1 kg and an average BMI gain of 0.35. Members of a student corps gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
3
32
1
4
Order By: Relevance
“…University students adopt unhealthy eating behavior in response to a range of individual, social and environmental factors (Deliens et al, 2014;Martinez, Harmon, Nigg, Bantum, & Strayhorn, 2016;Sogari, Velez-Argumedo, Gómez, & Mora, 2018), and may gain or lose weight (Brown, 2008;Gropper, Simmons, Connell, & Ulrich, 2012) in response to psychological stress (Boyce & Kuijer, 2015), changes in diet, and/or increased alcohol consumption (de Vos et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…University students adopt unhealthy eating behavior in response to a range of individual, social and environmental factors (Deliens et al, 2014;Martinez, Harmon, Nigg, Bantum, & Strayhorn, 2016;Sogari, Velez-Argumedo, Gómez, & Mora, 2018), and may gain or lose weight (Brown, 2008;Gropper, Simmons, Connell, & Ulrich, 2012) in response to psychological stress (Boyce & Kuijer, 2015), changes in diet, and/or increased alcohol consumption (de Vos et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is of particular importance, because unhealthy dietary behavior (e.g. low intakes of fruit and vegetables, and breakfast/meal skipping) among university students is associated with higher levels of stress (Lee et al, 2016) and lower academic achievement (Burrows et al, 2017), motivation to improve lifestyles (de Vos et al, 2015), and the ability to empathize with others (Brehm et al, 2016). Although university students typically demonstrate an awareness of the negative impact of unhealthy food intake, convenience and taste are often higher priorities that drive their consumption behavior (Abraham, Noriega, & Shin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An exaggeration on the data on some magazine articles and Internet Web sites regarding a gain of 15 lbs among freshman students can be seen. Although, actual weight gain has been found ranging from 1.6 lbs (0.73 kg) to 8.8 lbs (3.99 kg), some studies have even found that no significant weight gain occurs in the first year of college (6)(7)(8). The abnormal weight gain and obesity has been reported as an epidemic phenomenon according to the world health organization (WHO), with an approximate number of 1.4 billion worldwide overweight and 300 million persons clinically obese (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been found to infl uence weight gain, including membership in student groups, which can create a less regular eating schedule; furthermore, students with irregular schedules are also less willing to change their eating habits when encouraged to make healthy choices. 12 Since cultural influences vary between countries and even between corps students and non-corps students, it is vital to study each population to increase the effectiveness of intervention. This is one of the first studies on weight and fitness in Korean university students.…”
mentioning
confidence: 99%